Für kommende zeiten - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2005)
FÜR KOMMENDE ZEITEN / FOR TIMES TO COME Intuitive Music(SHORTENING AWAKE HALT PRESENTIMENT INSIDE WAVES)(Ensemble for Intuitive Music Weimar)